Far - field modelling of the multicore optical fibre - Kochanowicz, Marcin; Dorosz, Dominik; Żmojda, Jacek (Photonics Letters of Poland, 2009)
In the paper the phase - locked emitters in multicore optical fibres for high power fibre lasers are presented. The influence of the normalized frequency and diameters of the cores on the shape of the pattern in the Fraunhofer diffraction region has been analysed. The highest amount of energy conducted in the supermode is obtained at possibly large diameters of the cores and at possibly low value of the normalized frequency.